The association between fecal incontinence and asthma among adult Americans: evidence from NHANES 2005–2010 - Wang, Na; Song, Yongfu; Xie, Xiaofei; Wang, Zhuang; Wang, Yongji (Frontiers in Medicine, 2025)
ObjectivesThere is a paucity of research exploring the relationship between fecal incontinence (FI) and asthma. This study seeks to evaluate the potential correlation between FI and asthma among adult Americans.MethodsUtilizing a cross-sectional design, this study comprised a sample of 11,128 adults aged 20 years and older sourced from the National Health and Nutrition Examination Survey (NHANES) conducted between 2005 and 2010. FI is characterized by the involuntary excretion of solid, liquid, or mucus stool occurring at least once a month. Adjusted odds ratios (OR) were calculated using logistic regression models. Subgroup analyses were performed to validate the robustness of the findings.ResultsAfter adjusting for baseline characteristics, lifestyle habits, and comorbidities, a significant association was observed between FI and an increased risk of asthma (OR: 1.33, 95% CI: 1.1–1.61, P = 0.003). Subgroup analysis revealed a significant correlation between FI in females and asthma (OR: 1.36, 95% CI: 1.06–1.73), and this correlation is particularly pronounced in middle-aged and elderly individuals, further supporting the association between FI and asthma.ConclusionWe found a significant positive correlation between FI and asthma. Females and individuals aged over 45 demonstrate an increased vulnerability to developing asthma. Prompt intervention for individuals experiencing fecal incontinence may mitigate the risk of asthma onset.